Economic Viability Analysis of Electric Bikes over Conventional Bikes - Kumar, Praveen (Journal of Electronic Voltage and Application, 2025)
In India, two-wheelers have taken over the transportation industry, with a large portion of the vehicles sold in the country and being used as a major means of transportation. The trend of sustainable transport in the world has made electric vehicles (EVs) an attractive alternative to internal combustion engine (ICE) vehicles, which can potentially save energy and minimize greenhouse gas emissions. Nevertheless, the lack of clarity in the total cost of ownership (TCO) is a barrier to EV adoption in India. The paper is a comparison of TCO of electric two-wheelers (E2Ws) and ICE bikes based on real-world models such as the Revolt RV400 and Honda CB Shine 125cc. The initial costs, running costs (electricity/fuel), and the cost of replacing the battery are calculated using a methodological cost framework, which is supported with the EV Calculator Pro application. The findings indicate that EV running costs (0.25-0.98/km) are 31-67 percent less than ICE costs (1.42-2.00/km), and the Revolt RV400 saves 67 percent compared to the Honda CB Shine. The costs of battery replacement (0.40-0.48/km) are also a major consideration. The paper finds that EVs can be cost-effective and is environmentally friendly and suggests that the policy measures, such as subsidies and charging networks, should be implemented to increase adoption.